NUMERICAL INVESTIGATION OF HEAD DIAMETER INFLUENCE ON TENSILE CAPACITY OF HEADED STUDS (Malaysian Journal of Civil Engineering, 2018)
Objective of this paper is comparison of results of numerical analysis of headed studs with different head size and CCD (Concrete Capacity Design) approach which is used for design of anchoring in Eurocode 2. The breakout simulation tests of six different head diameters with four different effective embedment depths were investigated. The concrete properties were kept constant for all of them. It was found that the capacity of anchor is affected by the head size significantly. The approximately 25% decrease of capacity for small heads and about 30% capacity increase for large heads were observed in comparison to the CCD method.